Knowledge, Attitudes and Practice of Healthcare Providers, Healthcare Regulatory Practitioners and Patients Toward Biosimilars in China: Insights From a Nationwide Survey - Yang Hu; Yang Hu; Yang Hu; Yang Hu; Zaiwei Song; Zaiwei Song; Zaiwei Song; Dan Jiang; Dan Jiang; Dan Jiang; Dan Jiang; Lin Zhuo; et al. (Frontiers Media S.A., 2022)
Objective: With increasing numbers of biosimilars entering the market or in the approval pipeline in China, understanding the current awareness and attitudes of biosimilars still remains the first step to promote uptake. This study aims to investigate the knowledge, attitudes and practices (KAP) of multiple stakeholders toward biosimilars, including healthcare providers (HCPs), healthcare regulatory practitioners and patients, and to provide practical information for future uptake of biosimilars in China.Methods: This nationwide cross-sectional online survey was conducted in mainland China. The questionnaire with a high level of reliability and validity was designed based on previous studies and clinical questions in the Clinical Practice Guideline for Clinical Application of Biosimilars. Logistic regression model was employed to identify possible impact factors, and Spearman's rank correlation test was used to identify the correlation between knowledge and attitudes. Chi-squared test was used to compare the differences between different stakeholders.Results: Overall, 599 valid respondents were recruited, of whom 77.63%, 7.01% and 15.36% were HCPs, healthcare regulatory practitioners and patients, respectively. A total of 504 respondents who had heard of biosimilars were included in the KAP analysis. 76.70% of HCPs, 90.24% of healthcare regulatory practitioners and 50.98% of patients had good knowledge about the definition, while less familiarity with the development process and regulations on interchangeability and indication extrapolation was found in the former two groups. For attitudes toward biosimilars, an overall lack of positivity was shown, as only 18.20% HCPs, 14.63% healthcare regulatory practitioners and 23.53% patients were classified as having positive attitudes. More specifically, most respondents were positive about the influence of payment policy on the uptake of biosimilars, but they showed a neutral attitude toward the clinical medication and interchangeability of biosimilars. Efficacy, safety, immunogenicity, interchangeability and indication extrapolation are major concerns when utilizing biosimilars. Regarding practice, our study showed an inadequate utilization of biosimilars in China. Several further suggestions on the regulation of biosimilars were proposed by healthcare regulatory practitioners.Conclusions: There is still plenty of room for improvement of knowledge, attitudes and practice toward biosimilars among multiple stakeholders in China, which can be improved through high-quality real world evidence, educational programs and other effective measures directed towards barriers.